Simple simultaneous determination of iron and manganese by sequential injection spectrophotometry using astilbin extracted from Smilax china L. root - Lucksagoon Ganranoo (2018)
© 2018 Elsevier B.V. Simple simultaneous determination of iron and manganese by sequential injection spectrophotometry using astilbin extracted from Smilax china L. root is proposed. It is based on the kinetic difference of the complexation of the ions and astilbin. With a simple sequential injection system, the simultaneous determination can be performed at pH 10 and can be followed at a wavelength of 440 nm. A throughput of 12 samples per hour was obtained with detection limits (3σ) of 0.05 mg L−1 iron(III) and 0.20 mg L−1 manganese(II), respectively. Application of the proposed system to real ground water sample was demonstrated. The results agreed with that of the atomic absorption spectrophotometric reference method.